Characterization and Biological Performance of Marine Sponge Collagen - Fernandes,Kelly Rossetti (2021)
Abstract This study characterized the morphological aspects of marine collagen - spongin (SPG) extract from marine sponges, as well as, evaluating its in vitro and in vivo biological performance. Aplysina fulva marine sponge was used for the SPG extraction. It was investigated the physicochemical and morphological properties of SPG by using scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction and compared to PMMA and bovine collagen. Additionally, the SPG cytotoxicity and its influence on cell proliferation, through in vitro tests. Moreover, the in vivo biological response was investigated using an experimental model of tibial bone defect. The results demonstrated that SPG presented an irregular granular aspect, with a composition of OH, C=O, NH, CN and an amorphous profile. Also, in vitro viability results for the L929 and MC3T3 cell lines cultured with SPG extracts demonstrated normal growth in comparison to controls, except for MC3T3 viability at day 3. For in vivo analysis, using tibial bone defects in rats, SPG treated animals presented an increased rate of material resorption and higher granulation and bone formation deposition in the region of the defect, mainly after 45 days. As a conclusion, SPG was successfully extracted. The in vitro and in vivo studies pointed out that SPG samples produced an increase in L929 and MC3T3 viability and improved the performance in tibial bone defects. It can be concluded that SPG can be used as a bone graft for bone regeneration.